PEMBINGKAIAN ATLET PEREMPUAN PADA AJANG OLIMPIADE TOKYO 2020 DI MEDIA ONLINE OKEZONE.COM DAN KOMPAS.COM - Chrisintya Mauli Sitorus; Wiwid Noor Rakhmad; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Media reporting on female athletes still has some problems. Starting from stereotypes, sexism, objectification, commodification, and their voices that aren't represented proportionally. In Indonesia, the masculine culture embedded in sports and media often ignores the abilities and achievements of female athletes. This study used the critical constructivism paradigm to find out how female athletes are represented through the framing in the online media Okezone.com and Kompas.com during the 2020 Tokyo Olympics. This study used Zhongdang Pan and Gerald M Kosicki's framing analysis. This model divides framing into four elements; syntactic structure, script structure, thematic structure, and rhetorical structure. Ten news, each from online media Okezone.com and Kompas.com from 22 July - 23 August 2021 used as data for this study. Findings from this study indicate that news titles published by Okezone.com are the result of commodification based on the objectification of female athletes' physical appearances. This can be seen through the syntactic structure used in headlines and leads. The dominant script structure prioritizes